Efektivitas Rendaman Biji Ketumbar (Coriandrum Sativum L) Untuk Terapi Masalah Keputihan Pada Wanita Usia Subur - Dewi Andang Prastika; Sugita Sugita (Poltekkes Kemenkes Surakarta, 2018)
Abstract: Vaginal Discharge, Coriander Seeds, Coriander Seeds Soaking Water, Women Of Childbearing Age. The number of women in the world who have experienced vaginal discharge about 75%, this also happens in Indonesia that as many as 75% of women experience vaginal discharge. Later, herbal ingredients into the solution of choice for health problems in the community. Coriander seeds contain very good in solving problems. Aim this research is to determine the effectiveness of immersion coriander seed towards healing vaginal discharge in women of childbearing age. This research uses quasi-experimental design with static design Comparation group. These samples included 60 respondents, the sample was divided into two groups: control group and the intervention group. The sampling technique used in this research is accidental sampling. The average incidence of vaginal discharge in the control group occurred within 10.27 days with standard deviations 3.903 while the intervention group average incidence of vaginal discharge occurs more quickly over a period of 4.63 days with standard deviations 2,059. Results of analysis using t test showed p value of 0.000 (<0.05) or the Sig 0,000 less than 0.05, then the soaking water coriander seeds statistically effective in solving the problem of vaginal discharge in women of childbearing age. Of testing using the t test showed that the soaking water coriander seeds effective to solve the problem of vaginal discharge in women of childbearing age.